CLINICAL VALUE OF IMMUNE PROFILING IN PATIENTS WITH RECURRENT UPPER RESPIRATORY TRACT INFECTIONS - I. A. Novikova; T. S. Petrenko (Медицинская иммунология, 2014)
Abstract. We have observed eighty-nine patients with chronic recurrent infections of upper respiratory tract. Multiple immune parameters were evaluated during remissions of the disease. Increase in relative and absolute CD3+CD4+CD25+, CD3+HLA-DR+, CD3+CD16/CD56+ counts of blood lymphocytes, as well as higher concentrations of circulating immune complexes (CIC), along with decreased serum IgM and IgG levels were observed among the patients, as compared with appropriate parameters of control group. However, the major lymphocyte subsets did not differ between patients and controls. Hence, a content of CD3+CD16/CD56+ lymphocytes proved to be the most informative immunological parameter in the patients, since their levels directly correlate with duration of the disease and exacerbation rates. Meanwhile, CD3+СD16/СD56+cell counts show a negative correlation with the total numbers of B-lymphocytes and IgM concentrations in peripheral blood.